2023
DOI: 10.1080/15502783.2023.2206802
|View full text |Cite
|
Sign up to set email alerts
|

Can the supplementation of vitamin D, sun exposure, and isolation during the COVID-19 pandemic affect the seasonal concentration of 25(OH)D and selected blood parameters among young soccer players in a one-year training season?

Abstract: Objective This study examined the effect of vitamin D supplementation, sunlight radiationradiation, and home isolation during the COVID-19 pandemic on the seasonal changes in 25(OH)D concentration and selected biomarkers in young soccer players along a one-year training cycle. Method Forty elite young soccer players (age: 17.2 ± 1.16 years, body mass: 70.2 ± 5.84, and body height: 179.1 ± 4.26 cm) participated in the research. Only 24 players completed the measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…The same study also demonstrated that, in the case of low vitamin D values, oral supplementation decreases the risk of stress fractures [ 36 ]. Vitamin D supplementation, sunlight radiation and monitoring vitamin D levels are important factors to consider during a football season that allow the athlete to maintain good performances [ 37 , 38 ]. Monitoring vitamin D can be useful for identifying potential declines, and, if necessary, providing individual supplementation plans for athletes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same study also demonstrated that, in the case of low vitamin D values, oral supplementation decreases the risk of stress fractures [ 36 ]. Vitamin D supplementation, sunlight radiation and monitoring vitamin D levels are important factors to consider during a football season that allow the athlete to maintain good performances [ 37 , 38 ]. Monitoring vitamin D can be useful for identifying potential declines, and, if necessary, providing individual supplementation plans for athletes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%